Tadaluring Microteaching: An Effective Learning Model to Develop Basic Teaching Skills - Arifmiboy Arifmiboy (Jurnal Pendidikan Teknologi dan Kejuruan, 2019)
This study explored the effect of using a Tadaluring microteaching learning model on mastering a number of basic teaching skills by prospective teachers. The Tadaluring microteaching learning model is a learning model which combines three forms of integrated training namely classroom practices, online practices, and offline practices. This study was classified as a quasi-experimental study with a non equivalent control group design. The sample was selected with a purpose-sampling technique. The data were analyzed using a t-test method. The results of the study were: (1) there is a significant effect of using a Tadaluring microteaching learning model on prospective teachers' basic teaching skills, (2) the average ability to master basic teaching skills of prospective teachers using the Tadaluring model was higher than 80 with a very effective interpretation used in microteaching learning.